SAGE ESSENTIAL OIL EXHIBITS ANTIOXIDATIVE AND ANTIMICROBIAL ACTIVITY IN CHICKEN COOKED SAUSAGES - Šojić, Branislav; Škaljac, Snežana; Jokanović, Marija; Pavlić, Branimir; Eva, IVANIŠOVÁ; Monika, BOŽIKOVÁ; Savanović, Danica; BINCZARSKI, Michal (Journal on Processing and Energy in Agriculture, 2025)
Sage (Salvia officinalis L.) represents medicinal plant from Lamiaceae family, which has been recognized for various biological activities due to its complex chemical profile. Besides widely used application in pharmaceutical industry, sage has found application as flavoring agent in food products. The effect of sage essential oil (SEO) obtained from sage (Salvia officinalis L.) on antioxidative and antimicrobial activity in cooked chicken sausages was investigated. pH, instrumental parameters of color (CIE L*, CIE a* and CIE b*), thiobarbituric acid-reactive substance (TBARS) value, microbial profile and sensory panel scores were examined. The addition of SEO in concentrations from 0.010 to 0.100 µl/g significantly (p
Keywords: sage essential oil; cooked sausage; novel antioxidants; antimicrobial activity